Pengakuan Petrus Dan Tomas Tentang Yesus Sebagai Tuhan: Fondasi Teologis bagi Iman Jemaat di Tengah Pluralisme Agama - Tobing, Jhon Piter; Yusup Amasia Mayopu (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
In the increasingly complex context of religious pluralism, a firm confession of faith in the divinity of Jesus is the primary foundation for the life of the Christian congregation. This study aims to examine the theological meaning of Peter's (Matthew 16:16) and Thomas' (John 20:28) confession of Jesus as Lord, and its relevance for strengthening the congregation's faith amidst the reality of religious diversity. Using a theological-biblical approach and qualitative-descriptive methods, this study explores how the two disciples' statements of faith reflect the core of New Testament Christology and serve as the basis for the church's confessions of faith throughout history. The results of the study indicate that Peter's confession as